2015
DOI: 10.1155/2015/480418
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Bilirubin and Estimated Glomerular Filtration Rate among Diabetic Patients

Abstract: The subjects comprised 230 men aged 77 ± 10 (range: 50–100) years and 279 women aged 81 ± 10 (50–101) years that visited the medical department. We examined the relationship between increased serum bilirubin and renal function evaluated by estimated glomerular filtration rate (eGFR) using CKD-EPI equations modified by a Japanese coefficient. Compared with the fourth quartile in serum bilirubin (1.01–1.97 mg/dL), the nonadjusted, age and gender-adjusted, and multivariate-adjusted odds ratios {95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Patients having lower serum total bilirubin were found to be 2.23-times more likely to develop diabetic kidney disease than patients with a high serum total bilirubin level. This is supported by the findings of Takeaki et al 19 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients having lower serum total bilirubin were found to be 2.23-times more likely to develop diabetic kidney disease than patients with a high serum total bilirubin level. This is supported by the findings of Takeaki et al 19 …”
Section: Discussionsupporting
confidence: 89%
“…Patients having lower serum total bilirubin were found to be 2.23-times more likely to develop diabetic kidney disease than patients with a high serum total bilirubin level. This is supported by the findings of Takeaki et al 19 Uric acid (UA) is the end product of purine metabolism in humans, and its high serum levels (hyperuricemia) are classically related to the precipitation of crystals in the joints, leading to arthritis. 20 In our study it was observed that there is a significant mean value difference (p<0.001) and the serum uric acid level was observed to be higher in patients with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 58%
“…Japanese diabetic patients reported a positive association between serum bilirubin and eGFR. 23 Our findings were consistent with previous study, which imply an important protective effects of bilirubin on the progression of diabetic nephropathy.…”
supporting
confidence: 93%
“…The renal protective effect of BIL has recently attracted much attention. Higher serum BIL within the normal range is associated with less ABU and less deterioration in glomerular function in both type 1 and type 2 diabetic patients [ [11] , [12] , [13] , [14] , [18] , [19] , [20] ]. Because most of the relevant studies have been reported in Japanese populations, a large-scale single-center database cohort study from Taiwan was conducted to evaluate a possible ethnic difference in results and to assess the relationship between serum BIL and AUPr in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%